MRI for the assessment of placental blood flow in diabetic pregnancies. (7th June 2011) - Deshpande, R; Anblagan, D; Jones, N W; Costigan, C; Raine-Fenning, N; Mansell, P; Leach, L; Gowland, P; Bugg, G
Abstract : Introduction: Optimal placental blood flow is essential for adequate materno-fetal nutrient exchange and a successful gestation. In maternal diabetes the placenta is often large with abnormal vascular development. To date, it has not been possible to study placental blood flow in detail, but MRI potentially provides such a technique. Aims: To compare blood flow within the placenta in diabetic and control pregnancies using MRI. Methods: Six women with diabetes and six controls had MRI scans at 24–26 weeks. A 1.5 T Philips Achieva MRI scanner was used. The IVIM sequence was respiratory gated, standard diffusion pulsed spin echo sequence acquired with five transverse slices encompassing the placenta at 12 b values, repeated five times. Analysis was performed to calculate the fractional moving blood volume (f, range 0–1) in each voxel of the entire placenta. Results: The mean value of f in the two groups was similar; control (0.37) and diabetic (0.34). The women with diabetes had wider distributions of f with a lower mode (0.26 vs 0.32, p=0.04) and a borderline increased fraction of voxels with very high perfusion (f >0.8) at 4.1% vs 2.5% in controls (p=0.06). Conclusions: We have for the first time antenatally demonstrated a difference in the distribution of placental blood flow in women with diabetes using MRI. It is possible that the high velocity blood flow observed in some intervillous spaces is of pathological significance. MRI provides a potentially valuable tool for the investigation of placental blood flow.